Association between body roundness index and phenoage acceleration among US adults - Yifei Tan; Yifei Tan; Ni Zeng; Ni Zeng; Shiwen Yu; Chaoban Wang; Chaoban Wang; Xintong Jia; Xintong Jia (Frontiers in Public Health)
BackgroundPhenoage, compared to chronological age, better captures the multifaceted nature of aging as a process influenced by various pathological and environmental factors. Phenoage acceleration, defined as the disparity between biological and chronological age, indicates aging pace. However, the association between body roundness index (BRI), a more precise measure of obesity, and phenoage acceleration remains unexamined.MethodsAdults participants were enrolled from the United States National Health and Nutrition Examination Survey (NHANES) conducted between 2005 and 2020. The values of BRI, as well as body mass index (BMI) and phenoage acceleration were calculated. Potential correlations between phenoage acceleration and the values of BRI were explored using multivariate regression models.ResultsData from 8,848 individuals were analyzed, of which 4,271 (48.3%) participants being female. The overall mean BRI among participants was 5.43 (±2.37), while the mean phenoage was 45.5 (±18.5) years. After full covariate adjustment, a stepwise increase in phenoage acceleration was observed across BRI quartiles. Compared to Quartile 1 (Q1, reference), the acceleration was significantly greater in Q2 (β = 1.68, 95% CI: 1.25–2.11), Q3 (β = 3.65, 95% CI: 3.20–4.09), and Q4 (β = 6.64, 95% CI: 6.18–7.10), indicating a progressively faster aging rate with higher BRI levels. Across all subgroups, higher BRI values were consistently associated with an increase in phenoage acceleration.ConclusionOur study reveals a significant positive link between BRI and phenoage acceleration, highlighting BRI’s potential as a sensitive predictor of biological aging. Integrating BRI into routine assessments could enable more personalized and effective strategies for healthy aging.